Parental emotional competence and parenting in low-income families with adolescents - Kliewer, Wendy (J Fam Psychol, 2015)
Ample research has demonstrated that alexithymia, which is characterized by difficulty processing emotions, is associated with disruptions in parenting infants and toddlers. Individuals suffering from alexithymia have among other negative outcomes difficulty building and maintaining interpersonal relationships. Research on emotional expression and recognition has documented the importance of these competencies for the quality of the parent-child relationship and for skills critical for parents of adolescents, such as effective monitoring. However, literature linking parental alexithymia to parenting behaviors and related constructs during adolescents is lacking. The present study closes this gap by examining how mothers’ (M age = 39.42 yrs, SD = 7.62; Range = 23–67) alexithymia affects parent-reported behaviors of solicitation and control, as well as youths’ (53.6% female; M age = 12.13 yrs, SD = 1.62; Range = 9–16) reported disclosure and felt acceptance by their mothers among a sample of 358 primarily urban, African American families. Structural Equation Models revealed that mothers’ alexithymia was prospectively related to less parental solicitation two years later for both males and females, and to lower levels of felt acceptance for males. Multiple group analyses revealed that these models fits equally well for younger and older youth. Contrary to hypotheses, alexithymia was not related to control or to disclosure. Taken together, these findings indicate that parents’ difficulty in processing emotions contributes to parenting beyond early childhood.